Fleet‐wide acceptance of escape gaps and their utility for reducing bycatch in south‐eastern Australian Portunus armatus traps. (19th July 2022) - Barnes, Thomas C.; Broadhurst, Matt K.; Johnson, Daniel D.
Abstract: In response to widescale, voluntary uptake of escape gaps by commercial trappers using collapsible netted cylindrical (or "round") traps targeting blue swimmer crabs, Portunus armatus, in south‐eastern Australia, an observer‐based study was used to assess the adoption and effectiveness of the most common escape gaps across two estuaries responsible for >70% of all harvest. Five observers collected data from 5710 deployments of round traps over 116 days. Among 60% of round traps with escape gaps, 73% were rectangular shaped, and the rest were either circular or square. Catches were dominated by P. armatus (93%), but ~60% were undersized (<65‐mm carapace length; CL). Compared with round traps with no escape gaps, traps with a rectangular design consistently retained fewer undersized P. armatus (by up to 54%); similar to earlier, manipulative experiments. However, unlike previous observations, escape‐gap performance did not significantly improve with increasing catches of P. armatus . Eventual 100% adoption of escape gaps should enable large numbers of undersized P. armatus to escape traps and avoid discarding each year in south‐eastern Australia.